RETRACTED ARTICLE: Interrelationships between urban policy and climate, with emphasis on the environment - Hassan Kamran Dastjerdi; Narjessadat Hossaini Nasrabadi (City, Territory and Architecture)
Abstract There is growing evidence that projected climate change has the potential to significantly affect public health. Many of these effects are likely to be exacerbated by the risks associated with exposure to heat, floods, and chemical and biological pollution in cities. Identifying the effects of climate change on the environment, and the risks and opportunities of adapting to mitigating climate change can help city policies and planning. The stability of urban systems may be jeopardized if appropriate measures are not taken with the urban climate in the field of environment. Studies show that urban life has always been closely related to the natural environment. One of the most important natural factors involved in the typology of cities, which has a very influential role, is climate. In fact, the characteristics and conditions of geographical spaces, especially cities, are due to the natural and abnormal natural possibilities and limitations of natural geographical factors. Because the city originates from the mathematical and relative position, natural factors, especially climate, have a great impact on the typology and natural and human characteristics of cities. In this fundamental article, a descriptive-analytical method has been tried to examine urban space policies with emphasis on the environmental field. The question that arises here is what effect does climate change have on the type and method of policy- making and policy of urban managers in the field environmental? The results show that cities are climatically divided into desert, mountainous and coastal cities that have their own economic and social characteristics. Since environmental issues in any country are largely due to natural conditions and the characteristics of the human environment, knowledge of natural geography and an understanding of the dialectical relationships between the environment and humans are important for analyzing geographical issues. And has a significant role in managing space policy, especially urban space.